Gender Citra Perempuan dalam Lagu Campursari, Analisis Wacana Kritis - Wahyuningsih, Sri (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to analyze the campursari song “Mangku Purel” using Sara Mills' critical discourse analysis approach consisting of subject-object positions and reader positions to see the gender image of women who experience marginalization, subordination, stereotyping, and social burdens in social environmental groups. This study has a problem formulation of how the gender image of women in the campursari song "Mangku Purel" through Sara Mills' critical discourse analysis. The method used in the study is descriptive with a qualitative approach using Sara Mills' critical discourse analysis consisting of subject-object positions and reader positions to see the gender image of women who experience marginalization, subordination, stereotyping, and social burdens in social environmental groups. The results of the analysis show that the campursari song "Mangku Purel" is a gender image of women who experience marginalization, subordination, stereotyping, and social burdens in social environmental groups. Women as wives are labeled as women who must obey because as weak women who need the role of men as providers of breadwinners and security. Including marginalization where women are not the backbone of the family or may be felt by their husbands as a burden on their lives. Lastly, psychological violence is due to mental pressure that is often hurt by the husband.